A study of prognostic significance of serum magnesium and serum potassium levels in acute stroke - Sudhanshu Subrat; Manohar Lal Prasad; Kavya Varshney; Kanika Bansal; Mayank Mahajan; Anindya Chowdhury (Medical Laboratory Journal)
Background: Stroke is one of the major causes of morbidity and mortality worldwide. Various studies have examined the neuroprotective effects of magnesium and potassium ions through their effects on the glutamate receptor and the endothelium, achieved by lowering blood pressure and through their anti-inflammatory and anti-apoptotic properties. The objective of our study was to determine the prognostic significance of serum magnesium and serum potassium levels in acute stroke. Methods: An observational study was conducted at Rajendra Institute of Medical Sciences, Ranchi, for 18 months on 150 adults in patients with acute stroke, enrolled within 72 hours after applying appropriate inclusion and exclusion criteria. Correlations between the Modified Rankin Scale (mRS) score at discharge and the Glasgow Coma Scale (GCS) score at admission with serum levels of magnesium and potassium were calculated. Statistical analysis was performed using SPSS software version 27.0. Results: Two groups were formed based on serum magnesium levels: <1.5 mg/dL and >1.5 mg/dL. Similarly, two groups were created based on serum potassium levels: <3.5 mEq/L and >3.5 mEq/L. A significant correlation was found, using Spearman’s coefficient test, between serum potassium and magnesium levels and the GCS score at admission, as well as the mRS score at discharge (p < 0.05). Conclusion: Lower concentrations of magnesium and potassium are associated with increased cerebral arterial contraction and greater neurological damage.